Home advantage effect in Greek basketball leagues at the regular season: males vs. females and home vs. guest teams - Krommidas, Charalampos; Perkos, Stefanos; Karatrantou, Konstantina; Soulas, Eleftherios; Chasialis, Athanasios; Armenis, Elias; Gerodimos, Vassilis (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Home advantage may have an impact on gamerelated statistics and also on the psychological and behavioral state of competitors, coaches and officials. Aim of Study. The purpose of this study was to examine the home advantage effect in Greek professional basketball leagues and more specifically, to compare the game-related statistics between home and guest teams and between male and female ones in A1Greek basketball leagues during regular season. Material and Methods. Statistical data from males (A1: N = 182) and from females’ (A1: N = 88) basketball leagues were collected during 2014-2015 regular season. Results. Percentage of home wins was 61.5% for A1 males and 61.4% for A1 females’ basketball leagues, respectively. One way multivariate analyses of variance (MANOVA) revealed higher scores in free-throws (attempts and made), fouls (drawn), scored points and lower scores in fouls (committed) and turnovers, in-home teams than in guest ones of A1 male’s basketball league. Furthermore, home teams demonstrated higher scores in free throws (percentage), steals, scored points and fewer turnovers, compared with the guest ones in A1 female’s basketball league. Results also revealed that male teams had significantly better performance in most of the examined variables compared with the female teams playing at their home venue. Conclusions. The results of the present study may be used by Greek basketball coaches in order to prepare their players (physically, technically, tactically and mentally) more effectively
Keywords: home field; game-related statistics; gender; performance; basketball